PENGOLAHAN AIR BERSIH DI PONDOK PESANTREN HIDAYATUL MUSLIMIN 1 KABUPATEN KUBU RAYA DAN MA’HAD LABBAIK KOTA PONTIANAK - Ulli Kadaria; Suci Pramadita; Aini Sulastri (Jurnal Buletin Al-Ribaath, 2017)
Hidayatul Muslimin 1 Kubu Raya Boarding School and Ma’had Labbaik Pontianak have a problem in term of water quality. The limited quantity as well as the uncertainty of rainwater cause Hidayatul Muslimin 1 Boarding School and Ma’had Labbaik using well to use well to meet the needs of clean water. The physical quality of well water is dark brown in color because of the peat soil around both of locations. Well water is only pumped toward the reservoir without any water treatment process, thereby potentially causing diseases such as itching as well as causing yellow color in clothing and kitchen utensils. Thus, installation of water treatment unit is needed to treat well water into the clean water which is suitable for everyday use. Treatment technology used are chlorination, aeration, and filtration using clamshell media, with a processing capacity of 1000 liters. The method used is the participatory method by involving students in socialization, operation, and maintenance of water treatment installation. The physical quality of water is clean after treatment and suitable for everyday use. Keywords: Aeration, Filtration, Chlorination, Water Treatment